Cuff-assisted versus cap-assisted colonoscopy for adenoma detection: results of a randomized study - Sola-Vera, Javier; Catalá, Lourdes; Uceda, Francisco; Picó, María Dolores; Pérez Rabasco, Estefanía; Sáez, Jesús; Jiménez, Nuria; Arjona, María Dolores; Fernández, María; Girona, Eva; García-Sepulcre, Mariana Fe (Endoscopy, 2019)
Background The adenoma detection rate (ADR) is the most important marker of colonoscopy quality. Devices to improve adenoma detection have been developed, such as the Endocuff and transparent cap. The aim of the current study was to examine whether there was a difference in ADR between Endocuff-assisted (EAC) and cap-assisted colonoscopy (CAC).Methods A randomized prospective trial was conducted. Eligible patients included adults ≥ 18 years referred because of symptoms, surveillance, or colonoscopies as part of the Bowel Cancer Screening Programme (BCSP). The primary outcome measure was ADR. Secondary outcomes included mean number of adenomas, mean number of polyps, polyp detection rate, cecal intubation rate, and time to cecal intubation. Procedural measures, device removal rate, and adverse events were also recorded.Results A total of 711 patients (51.1 % men; median age 63 years) were included, of whom 357 patients were randomized to EAC and 354 patients to CAC. In the intention-to-treat analysis, the ADR was similar in both groups: EAC 50.4 % (95 % confidence interval [CI] 45.1 – 55.7) vs. CAC 50.6 % (95 %CI 45.2 – 55.9). Similar results were obtained in the per-protocol analysis: EAC 51.6 % (95 %CI 46.2 – 57) vs. CAC 51.4 % (95 %CI 46 – 56.8). There were no differences between the two devices in ADR according to the mean number of adenomas and polyps per procedure, polyp detection rate, cecal intubation rate, and time to cecal intubation. Device removal rate and adverse events were also similar.Conclusion In this randomized study, no differences in ADR were found between Endocuff- and cap-assisted colonoscopy.